Ireland’s “economic miracle” and globalisation - György Simon Jr (Međunarodni Problemi, 2005)
The paper gives a comprehensive picture of fundamental issues connected with the Irish “economic miracle”, with especial regard to globalisation effect. The analysis of Ireland’s economic development in the period from 1960 to 2003 answers the question why it decelerated, instead of accelerating, for a long time: two decades after the accession to the European Community in 1973 and mainly the enigma, the “economic miracle” why the rate of growth accelerated in the decade after 1993 to an extent (on annual average to almost 8 percent) similar to that previously observed only in East Asia. The country has not only caught up economically with the European Union, but has approximated the level of development of the United States. The analysis shows that all this can be attributed not only to Ireland’s favourable conditions, but also to an adequate economic policy and foreign direct investment. The author reveals the so-called globalisation effect that in Ireland after 1993 had a decisive role in the extraordinary acceleration of economic growth.